(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article examines the state of rural administration at the beginning of the twentieth century in Turkestan based on materials from Senator K.K. Palen. The work examines a specially compiled “Program for the revision of volost and rural institutions.” The article examines archival materials stored in the funds of the Russian State Historical Archive.